Fiqh Review on The Use of Sharia Credit Card Based on Fatwa DSN MUI No: 54/DSN-MUI/X/2006 - Harahap, Soritua Ahmad Ramdani; Azmi, Muhammad Ulul; Lahuri, Setiawan bin (AL-IKTISAB: Journal of Islamic Economic Law, 2019)
This study describes the fiqh review in the use of Islamic credit cards. In general, the opinions of leading scholars state that credit card transactions can be categorized in the kafalah, wakalah, hawalah, qardh, and ijarah agreements. These contracts are legally permissible and their use is adjusted to the transaction. In this study using a type of qualitative research with a literature study method approach. The results of this study explain that Islamic credit cards should be able to maintain the principle of utility in their using. This is based on the perspective of the principle of maslahah, which not only sees direct benefits or worldly benefits, but also sees benefits for the hereafter. So that there is a balance between the world and the hereafter in the fortified by ad-dharurat al-khams, namely preserving religion, soul, reason, descent, and wealth.